The Neonatal Microbiome: Implications for Neonatal Intensive Care Unit Nurses. Issue 6 (November 2017) - Rodriguez, Jeannie; Jordan, Sheila; Mutic, Abby; Thul, Taylor
Abstract : Abstract: Nursing care of the neonate in the neonatal intensive care unit (NICU) is complex, due in large part to various physiological challenges. A newer and less well-known physiological consideration is the neonatal microbiome, the community of microorganisms, both helpful and harmful, that inhabit the human body. The neonatal microbiome is influenced by the maternal microbiome, mode of infant birth, and various aspects of NICU care such as feeding choice and use of antibiotics. The composition and diversity of the microbiome is thought to influence key health outcomes including development of necrotizing enterocolitis, late-onset sepsis, altered physical growth, and poor neurodevelopment. Nurses in the NICU play a key role in managing care that can positively influence the microbiome to promote more optimal health outcomes in this vulnerable population of newborns. Abstract : Nursing care of babies in the neonatal intensive care unit (NICU) is complex, due in large part to various physiological challenges, including the neonatal microbiome, the community of microorganisms, both helpful and harmful, that inhabit the human body. Nurses in the NICU play a key role in managing care that can positively influence the microbiome to promote more optimal health outcomes in this vulnerable population of newborn babies.